Investigation of dihydrogen interactions with activated graphitic nanostructures and novel metal-organic frameworks - Telepeni, Irvin Petelo Lose (2009)
Hydrogen is an ideal energy carrier as it only produces water as a by-product. However, technical and social issues first need to be overcome in order to achieve such economy. In particular, this work focuses on solid state hydrogen storage as it is a key technological challenge. Herein, potential candidates currently investigated are porous materials that physisorb molecular hydrogen with fast kinetics and good reversibility in order to meet mobile transportation requirements. The goal is to be able to optimize the sorption properties of a compound by tuning critical parameters such as its pore size and/or its specific surface area. Carbon nanofibres were investigated as potentially cost-efficient materials. Engineering routes such as the integration of hetero-species by nitrogen doping and exfoliation / intercalation were performed on various carbon nanostructures affecting the surface topology of the engineered compounds compared to the as-prepared materials although the excess uptakes at 77 K and 20 bar remained low ca. 0.6 wt. %. Metal-organic frameworks are a promising class of porous materials and are currently strong competitors as hydrogen storage media thanks to their flexibility in structure design. A series of Cu (II) - frameworks have been found to have exceptional sorption properties at 77 K and 20 bar up to 7 wt. %. The successful combination of neutron techniques at NIST-CNR and ISIS-RAL enabled a clear insight of the adsorption site distribution of two Cu (11) - frameworks using para-H2 and D2 as probing gases. A common feature for the MOFs investigated was that dihydrogen preferentially coordinated to the exposed metal centres ca. 2.4 Å, followed by sorption at two discrete sites located within triangular windows connecting the MOF cavities. It revealed the co-existence of preferential site-specific with non-site specific adsorption within the pore structure which is different from the common concept of dihydrogen interacting with a homogeneous surface. It was also possible to follow the dynamics of hydrogen molecules at different coverage of the surface through the rotational transitions of the para-H2 molecule.